Beneficial effects of artichoke on liver phosphatidate phosphohydrolase and plasma lipids in rats fed by lipogenic diet - Esfandiar Heidarian,; Effat Jafari-Dehkordi,; Ali Seidkhani-Nahal, (International Journal of Phytomedicine, 2011)
Artichoke (Cynara scolymus L.) is full of natural antioxidants and has a lipid-lowering effect. The aim of this study was to investigate the effect of artichoke on the liver phosphatidate phosphohydrolase, plasma lipid levels, plasma malondialdehyde, and plasma antioxidant in rats fed by lipogenic diet. Male rats were fed by standard pellet diet (group I), standard diet supplemented with 10% artichoke (group II), lipogenic diet (containing sunflower oil, cholesterol and ethanol) plus 10% artichoke (group III) and only lipogenic diet (group IV). On day 60 of the experiment, liver phosphatidate phosphohydrolase activity, liver triglyceride, plasma lipids, plasma malondialdehyde, and plasma antioxidant levels were measured. Phosphatidate phosphohydrolase activity, liver triglyceride, the ratio of total cholesterol to high density lipoprotein cholesterol, plasma total cholesterol and triglyceride levels were significantly decreased due to artichoke treatment in groups II and III compared to groups I and IV, respectively. Significant reduction in plasma malondialdehyde and significant elevation in plasma antioxidant power observed in groups II and III compared to groups I and IV, respectively. The results clearly indicated that artichoke can be useful for the reduction of phosphatidate phosphohydrolase activity and liver triglyceride. Also, artichoke has beneficial effects in the controlling of hyperlipidemia, abnormalities in lipid profiles and oxidative stress in hyperlipidemic regimes.